Art-induced psychological well-being: Individual traits shape the beneficial effects of aesthetic experiences - Serena Castellotti; Elisa Gragnoli; Giada Baglioni; Roberta Criminisi; Barbara Giangrasso; Maria Michela Del Viva (PLoS ONE, 2025)
Since the beginning of the last century, a wide variety of studies have provided evidence of the role of art in improving health and well-being. In this study, we engaged 92 young adults in a guided tour of a contemporary art exhibition, centered around human freedom themes, offering an immersive multi-sensory experience. We aim to discover potential immediate beneficial effects of such aesthetic experience on anxiety, empathy, and compassion, and investigate how these effects relate to visitors’ psychological traits. We also studied whether individual characteristics could explain differences in visitors’ behavioral responses – i.e., visit time and post-visit evaluations. Prior to the experience, we collected participants’ information about their art preferences, interests, and expertise, and assessed their psychological traits of curiosity, openness to experience, anxiety, empathy, and compassion. The visit was led by an expert guide, and participants’ behavior was recorded through mobile eye tracking. Standardized self-report scales were administered before and after the visit to measure art-induced benefits on psychological well-being. An ad-hoc post-visit questionnaire, including several dimensions (beauty, understanding, satisfaction, etc.), was finally administered. Results showed that state anxiety decreased following the visit, particularly among visitors with a high trait of anxiety. Empathic and compassionate feelings increased after the visit, particularly among visitors with initially low empathic abilities and low compassion for humanity. Participants with higher curiosity and openness traits tended to spend more time engaging with the artworks and gave overall more positive evaluations. Higher art-related dimensions were linked to stronger emotional reactions and a greater sense of satisfaction and personal enrichment. Our findings provide additional evidence of the impact of art enjoyment on well-being. Art experiences centered around deeply emotional human themes may indeed reduce anxiety and enhance other-oriented feelings. Importantly, psychological traits define clusters of people who may benefit more from experiencing such art exhibitions.